Evaluation of pearl millet (Pennisetum glaucum) genotypes and validation of screening methods for supra-optimal temperature tolerance at seedling stage - YADAV, ASHOK KUMAR; NARWAL, M S; ARYA, RAJESH KUMAR (The Indian Journal of Agricultural Sciences, 2013)
The supra-optimal temperatures at seedling stage in pearl millet are known to be the most important cause of poorcrop stands at farmers’ field which can be managed through developing high temperature tolerant pearl millet [Pennisetum glaucum (L.) R. Br emend Stuntz] varieties. Identification of the superior germplasm for heat tolerance is essential for effective manipulation through breeding. Field screening techniques and laboratory screening technique were simultaneously used for the evaluation of pearl millet genotypes. In the field conditions, screening for heat tolerance was done using Seedling Thermo-tolerance Index (STI) and Seed to Seedling Thermo-tolerance Index (SSTI), whereas membrane thermostability (MTS) was taken as index for heat tolerance in the laboratory technique. These three indices were highly correlated among themselves. STI values were invariably high, whereas SSTI has lower values, as it also covers the effect of under soil mortality (USM). The field based thermo-tolerance indexes also showed significant correlation with other growth characteristics of seedling. Based on our results, it could be suggested that membrane thermo-stability test (MTS) may be used for screening large number of genotypes or germplasm accessions. We also suggest, the field based screening techniques, indices STI and SSTI, should be performed for evaluation of germplasm before they are released. Cluster analysis and correlation showed that growth characteristics of seedling can also provide certain indications of heat tolerance in genotypes.